Antithesis in Modern English Graffiti - Юлія Торговець (Філологічні студії)
Graffiti is a cross-cultural phenomenon that transcends geographical and chronological boundaries, becoming extremely popular with artists, archaeologists, cultural anthropologists and even linguists due to the variety of forms it takes and limitless freedom of expression it offers. Despite the contradictory nature and mixed views on its value, the anonymous form and wide availability to the public make graffiti an effective communication tool and an exceptionally interesting research object. Artists often employ antithesis (stylistic opposition) that helps them gain a new, broader and at times paradoxical perspective on pressing social, political and environmental issues by finding the points of stark contrast. This study has been carried out to identify the stylistic peculiarities of modern English graffiti, focusing on the analysis of antithesis. The findings indicate that, in order to convey opposing ideas, artists tend to choose contextual antonyms over objectively contrasting pairs of root ones which can be explained by their novelty and extraordinary polarity. The study suggests that all the analysed cases of antithesis can be grouped into explicit (the juxtaposition of the ideas is expressed in the written part while the graphical one heightens the effect) and implicit (the written part opposes the graphical one and a complete understanding of the message encoded in the graffiti is impossible without careful examination of both of them). The research also offers insights into expressive means and stylistic devices that enhance the aesthetic effect of antithesis such as rhyme, alliteration, parallelism and framing.